Teaching Indonesian L2 Learners Academic Writing: A Proposed Instructional Model - Adaninggar Septi Subekti (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2022)
This article reports a proposed instructional model to teach the second language (L2) academic writing in education with citations and references to learners in English Education departments. The model is suggested to be implemented in two semesters in a row. In the first semester of the implementation, learners are to take essay writing and academic reading courses simultaneously. In the former, learners learn to write coherent and cohesive sandwich paragraphs, do peer reviews, and write five-paragraph essays in education without citations and references. In the latter, learners familiarise themselves with various academic sources, write in-text citations and reference lists using Microsoft Word Reference Manager, paraphrase and summarise information from journal articles, and write a short paragraph using citations and references. In the second semester of the implementation of the model, learners take an academic essay writing course which is the progressing combination of the two aforementioned courses in the previous semesters. In this writing course, learners write two 1,200-word essays in education with citations and references from at least five sources. During the implementation of the model, a no-plagiarism policy is upheld through teachers' emphasising on paraphrasing and checking learners' works with plagiarism checkers before submission. Gradual progress is continuously monitored through teachers' feedback on progress. All in all, the model emphasises step-by-step progress in L2 academic writing supported by ample writing preparation time and continuous feedback on progress.